发布网友 发布时间:2024-10-24 08:54
共6个回答
热心网友 时间:2024-11-06 01:47
ab(c^2-d^2)-cd(a^2-b^2)
=abc^2-abd^2-a^2cd+b^2cd
=(abc^2-a^2cd)-abd^2+b^2cd
=ac(bc-ad)+bd(bc-ad)
=(bc-ad)(ac+bd)
热心网友 时间:2024-11-06 01:44
解:原式=abc^2-a^2cd b^2cd-abd^2
=ac(bc-ad) bd(bc-ad)
=(bc-ad)(ac bd)
望采纳
热心网友 时间:2024-11-06 01:51
abc²-abd²-a²cd+b²cd
热心网友 时间:2024-11-06 01:45
abc^2-abd^2-cda^2+cdb^2=abc^2+cdb^2-abd^2-cda^2=bc(ac+bd)-ad(bd+ac)=(bc-ad)(ac+bd)
手动敲打,不懂可以问
热心网友 时间:2024-11-06 01:51
ab(c-d)-(a-b)cd
=abc-abd-acd+bcd
=(abc-acd)+(bcd-abd)
=ac(bc-ad)+bd(bc-ad)
=(bc-ad)(ac+bd)
热心网友 时间:2024-11-06 01:50